PENGARUH HARGA, PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI PELNAS PT. DUTA BAHARI SENTOSA - Maria Maria; Ngaliman Ngaliman (Zona Manajemen: Program Studi Magister Sains Manajemen Universitas, 2017)
This study aimed to examine the effect of pricing, promotion and service quality on consumer purchasing decisions. This study uses three independent variables, price, promotion and service quality with the dependent variable is the consumer purchasing decisions. The use of variables in this study is expected to determine how the process is going on and what the driving factors behind consumer purchase decisions on the PT. Duta Bahari Sentosa. Passenger ship samples Allya Express 1, 94 peoples. Samples were taken by sampling techniques. Data analysis method used is quantitative analysis, validity, reliability test, classic assumption test, multicoloniarity test, heteroscedasticity test, normality test, multiple linear regression analysis, t test, f-test coefficient of determination R2. Based on the results of data analysis showed that: the variable price has a significant impact on consumer purchasing decisions sig value of the t test of 0.018 < 0.05 promotion variables have a significant effect on consumer purchasing decisions with a value of 0,007 t test sig > 0.05 and the variable quality of service have a positive but not significant influence on consumer purchasing decisions sig t test value of 0.280 > 0.05. Based on the calculation Test f, together variable price, promotion and service quality has a positive and significant impact to the value of F sig 0.005 < 0.05.